A Geographic Information System Analysis of Accessibility to Community Pharmacy in Shiraz, Iran: Geographic accessibility to pharmacy in Shiraz - Khosro Keshavarz,; Abbas Kebriaeezadeh,; Amir Hashemi Meshkini,; Ramin Hayati,; Somayeh Dehghan, (Iranian Journal of Pharmaceutical Sciences, 2012)
Geographic proximity has been shown to be a significant factor in healthcare utilization and also one of the important dimensions in the concept of accessibility. In this study, we aimed to evaluate the geographic accessibility to pharmacies in city of Shiraz. A geographic information system approach was obtained to evaluate geographic accessibility to pharmacies. A stratified random sampling was conducted to choose adequate points as the representative of whole city to measure their distance in both pedestrian and driving condition to the pharmacies. To measure the pedestrian accessibility of selected blocks in Shiraz, different distances of 150, 300, 450, 600 and 750 meter, and to measure driving accessibility different network distances of 5, 10 and 15 min were considered as acceptable levels of geographic accessibility. In terms of pedestrian accessibility, the analysis showed that about 45% and 15% of sample blocks have accessibility to at least one pharmacy in their 750 meters in normal days and holidays, respectively, based on straight line distance. In terms of driving accessibility, our analysis indicated that in normal days and also in holidays about 98% of sample blocks in Shiraz have at least one pharmacy in their 15 min based on network analysis and considering traffic limitation. In spite of implemented policy by food and drug organization to distribute pharmacies equitably through the whole city, geographic accessibility to pharmacy doesn’t seem to be desirable in Shiraz and some other policies may be needed to make the situation better.